Constraining Spectral Models of a Terrestrial Gamma‐Ray Flash From a Terrestrial Electron Beam Observation by the Atmosphere‐Space Interactions Monitor. Issue 9 (8th May 2021) - Sarria, D.; Østgaard, N.; Kochkin, P.; Lehtinen, N.; Mezentsev, A.; Marisaldi, M.; Lindanger, A.; Maiorana, C.; Carlson, B. E.; Neubert, T.; Reglero, V.; Ullaland, K.; et al.
Abstract: Terrestrial Gamma ray Flashes (TGFs) are short flashes of high energy photons, produced by thunderstorms. When interacting with the atmosphere, they produce relativistic electrons and positrons, and a part gets bounded to geomagnetic field lines and travels large distances in space. This phenomenon is called a Terrestrial Electron Beam (TEB). The Atmosphere‐Space Interactions Monitor (ASIM) mounted on‐board the International Space Station detected a new TEB event on March 24, 2019, originating from the tropical cyclone Johanina. Using ASIM's low energy detector, the TEB energy spectrum is resolved down to 50 keV. We provide a method to constrain the TGF source spectrum based on the detected TEB spectrum. Applied to this event, it shows that only fully developed Relativistic Runaway Electron Avalanche spectra are compatible with the observation. More specifically, assuming a TGF spectrum ∝ E − 1 exp − E / ϵ, the compatible models have ϵ ≥ 6.5 MeV ( E is the photon energy and ϵ is the cut‐off energy). We could not exclude models with ϵ of 8 and 10 MeV. Plain Language Summary: Terrestrial Gamma ray Flashes (TGF), originating from thunderstorms, are the highest energy natural particle acceleration phenomena occurring on Earth. The production mechanism of TGFs is not well understood. When interacting with the atmosphere, TGFs produce secondary electrons and positrons, and a part gets bounded to Earth's magnetic field lines, and travels large distances in space. They can be detected by instruments on‐board satellites located at the right place (in a window of about 40 km) at the right time (in a window of a few milliseconds). This phenomenon is called a Terrestrial Electron Beam (TEB). By detecting the TEB, we can retrieve information about the TGF that produced it. In this article, we present the first TEB originating from a tropical cyclone and with the lowest energies ever recorded (down to 50 keV). We also provide a method to infer properties of the energy distribution of the source TGF (producing the TEB) based on the energy spectrum of the TEB. Applied to this event, it shows that only TGF energy spectra among the most energetic that were proposed are compatible, and we cannot exclude even more energetic events. Key Points: Observation of a Terrestrial Electron Beam (TEB) with a spectrum resolved down to 50 keV A method to constrain the energy spectrum of the source Terrestrial Gamma ray Flash (TGF) based on the detection of the associated TEB is presented Only TGFs originating from fully developed Relativistic Runaway Electron Avalanche models can explain the observation